2019
DOI: 10.1111/dar.12970
|View full text |Cite
|
Sign up to set email alerts
|

Harm from other people′s drinking among college students in India

Abstract: Introduction and Aims There is a paucity of studies on the harms experienced by college students from India due to others′ drinking, despite their increased risk. We studied the prevalence and correlates of harm from others′ drinking among college students in the state of Kerala, India. Design and Methods A total of 5784 students from 58 colleges completed a self‐administered questionnaire, which included the World Health Organization—Thai Health Harm to Others from Drinking Master Protocol and other structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Our review includes studies on nomophobia, an emerging mental health issue, which is echoed by contextual studies that finding increasing rates of substance use and technology addiction among youth due to urbanization in India [101]. Other studies focused on measuring prevalence, progression perceived harms of various disorders and conditions, including depression, anxiety and stress, [102,103] alcohol use, [104,105] body image disorders [106,107] and aggression, bullying and violence, [108] and correlates such as parental pressure to perform academically, [109,110], relationships, negative peer pressure, school environment and gender roles [110]. [111].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Our review includes studies on nomophobia, an emerging mental health issue, which is echoed by contextual studies that finding increasing rates of substance use and technology addiction among youth due to urbanization in India [101]. Other studies focused on measuring prevalence, progression perceived harms of various disorders and conditions, including depression, anxiety and stress, [102,103] alcohol use, [104,105] body image disorders [106,107] and aggression, bullying and violence, [108] and correlates such as parental pressure to perform academically, [109,110], relationships, negative peer pressure, school environment and gender roles [110]. [111].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The assumption of a coverage level of 90% is based on previous community/university studies conducted in the state of Kerala, which have reported a non-response/ missing response of 5-10%. 21,22 The National Mental Health Survey of 2016, the largest Indian epidemiological study to date, 23 was conducted in multiple states across the country and considered stratification and clustering, assuming a design effect of 3. Since the present survey was conducted in a single state, we assumed a design effect as 2.5.…”
Section: Methodsmentioning
confidence: 99%